Answer:
[tex]g(x)=24(2)^{x-1}+16[/tex]
Step-by-step explanation:
The transformation of functions consists in applying a factor to a function that can expand or contract the function vertically or horizontally, reflect it on the axes or translate it with respect to the original function.
In this case, the function must be expanded vertically by a factor of 4, for which it must be multiplied entirely by the given factor, as follows:
[tex]f(x)=6(2)^{x-1}+4[/tex]
[tex]g(x)=4*[6(2)^{x-1}+4][/tex]
[tex]g(x)=24(2)^{x-1}+16[/tex]